IL-23 Inhibitors for Moderate-to-Severe Plaque Psoriasis: A Review of Clinical Efficacy, Safety, and Tolerability - Sima D. Amin; Annika S. Silfvast-Kaiser; So Yeon Paek; Dario Kivelevitch; Alan Menter (European Medical Journal, 2019)
Psoriasis is a chronic, immune-mediated skin condition with systemic involvement, frequently requiring long-term treatment. At present, there are 11 biologic agents available for the treatment of moderate-to-severe psoriasis, which target specific inflammatory cytokines involved in the immunopathogenesis of the disease. Among these, three monoclonal antibodies specifically inhibit the p19 subunit of IL-23. IL-23 is a heterodimeric cytokine consisting of two subunits: IL-23p19 and IL-23p40. IL-23 plays a key role in the immunopathogenesis of psoriasis by activating Th17 cells, leading to stimulation of downstream cytokines involved in the systemic inflammation and keratinocyte hyperproliferation observed in psoriasis. Overall, the anti-IL-23 agents demonstrate rapid clinical improvement along with a favourable safety profile. This review has analysed data on the clinical efficacy, safety, and tolerability of the three IL-23 agents (tildrakizumab, guselkumab, and risankizumab) in the treatment of moderate-to-severe plaque psoriasis.